Comparative Efficacy, Patient-Specific Predictive Factors, and Long-Term Safety of Extracorporeal Shockwave Lithotripsy for Urinary Calculi: A Systematic Review of Technical Optimization and Clinical Outcomes - Mulya; Mutiara Farrah Dhiba (International Medical Journal Corp. Ltd, 2025)
Introduction Extracorporeal Shockwave Lithotripsy (SWL) remains a pivotal, non-invasive treatment modality for urolithiasis, having revolutionized the management of stone disease since its introduction in the 1980s (Preminger et al., 2024; Long & Matlaga, 2020). Despite its established role, the current clinical landscape sees SWL increasingly challenged by highly effective, though more invasive, endourological techniques such as Ureteroscopic Lithotripsy (URSL/RIRS) and Percutaneous Nephrolithotomy (PCNL). The enduring relevance of SWL hinges critically upon optimal patient selection and rigorous adherence to technical optimization protocols to maximize efficacy and minimize failure rates (Wang et al., 2020). Methods A systematic search compliant with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement was performed, synthesizing outcomes from high-level evidence studies, including meta-analyses encompassing a minimum of 15 randomized controlled trials (RCTs) (Li et al., 2023; Mokhtari et al., 2023). Data were extracted for 12 clinical outcomes. The quality of comparative trials was assessed using the Cochrane Risk of Bias tool, version 2 (RoB 2) (Higgins et al., 2024; Minozzi et al., 2022). Results Efficacy and Logistics: Contemporary endourological treatments generally yield higher efficacy; URSL/PCNL result in significantly superior overall stone-free rates (SFRs) compared to SWL, especially for stones exceeding 10 mm and those located in the lower pole calyx (Wang et al., 2015). SWL is associated with a significantly greater need for retreatment procedures, with an Odds Ratio (OR) of 0.08 favoring URSL (Li et al., 2023). However, SWL maintains substantial logistical advantages, including a significantly shorter operating time (Standardized Mean Difference -29.314 minutes favoring SWL) and shorter hospital stay (Mean Difference 1.14 days longer for URSL) (Mohamed et al., 2023; Li et al., 2023). Safety and Predictors: While overall complication rates are statistically similar across methods (Li et al., 2023), URSL carries a higher specific risk of perforation (OR 0.13 favoring SWL) (Mohamed et al., 2023). Successful SWL is highly predictable based on pre-treatment imaging, with optimal success linked to stone density HU < 1000 and SSD < 10 cm (Siddiqui & Ahmed, 2021; Türk et al., 2024; Ouzaid et al., 2014). Furthermore, technical refinement, such as decreasing the shock wave rate to 60 to 90 shocks per minute, substantially improves stone fragmentation efficacy (Long & Matlaga, 2020). Long-Term Safety: A significant association exists between SWL performed for nephrolithiasis and the development of new-onset hypertension, evidenced by an overall Relative Risk (RR) of 1.21 (95% CI 1.11–1.31) (Seo et al., 2021). This risk increases with the number of SWL sessions required (Rudnick et al., 2018). Conclusion Extracorporeal Shockwave Lithotripsy remains the optimal non-invasive intervention for highly favorable calculi (≤ 10 mm, low HU, short SSD), provided technical optimization is rigorously applied. For stones predicted to be resistant, early treatment pivot toward URSL or PCNL is warranted to maximize definitive stone clearance and to mitigate the potentially dose-dependent long-term risk of hypertension and the requirement for multiple auxiliary procedures.